Calbindin expression in developing striatum of zebra finches and its relation to the formation of area X. Issue 2 (6th December 2012) - Garcia‐Calero, Elena; Scharff, Constance
Abstract A sexually dimorphic network of brain regions controls learning and production of song in zebra finches. How this specialized song system evolved is unknown. To start addressing this question, we focused on developmental differences between the sexes, using the expression of the calcium‐binding protein calbindin (CB) during embryonic to adult stages to map out the early development of Area X, a male‐specific striatal structure. We related this pattern to the expression of three transcription factors, Pax6 and Islet1 to delineate the striatal radial domains, and Nkx2.1 as a marker for cells of pallidal origin. An incipient Area X‐CB+ domain became discernable at embryonic day 13 in the Islet1‐ventral striatal field. This region contained many Nkx2.1‐expressing cells with a morphology characteristic of migrating cells. Eight days after hatching (PHD) CB staining clearly delineated Area X. Another CB+ structure formed around PHD5 at the subpallial/pallial boundary. We call it the CB+striatal capsule (CB‐StC) and discuss its relation with the previously described striatal capsule in vertebrates. The CB cell population in both Area X and CB‐StC, but not in the surrounding striatum, colocalized with the striatal medium spiny neurons (MSNs) marker, D1‐receptor associated signaling protein dopamine‐and‐cAMP‐regulated phosphoprotein of 32 kDa, DARPP32. In females, CB‐positive cells were also present in the rostral striatum but did not coalesce into an Area X‐like structure. We discuss possible reasons for CB expression in MSNs in songbirds and mammals, but not described in chicken striatum. J. Comp. Neurol. 521:326–341, 2013. © 2012 Wiley Periodicals, Inc.